Preparation method and application of microcrystalline cellulose loaded pillararene / gold nanoparticle catalyst

The preparation of microcrystalline cellulose-supported columnar aromatic/gold nanoparticle catalysts through mechanical grinding methods solves the problems of cumbersome and unenvironmental protection in the prior art, and achieves efficient and environmentally friendly catalyst preparation and excellent catalytic performance.

CN119746928APending Publication Date: 2025-04-04YANGTZE NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411959730.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art requires the use of solvents and complex purification techniques when preparing gold nanoparticle catalysts, and the process is cumbersome and not environmentally friendly.

Method used

The microcrystalline cellulose-supported columnar aromatic/gold nanoparticle catalyst was prepared by mechanical grinding method. The catalyst preparation was achieved by sonicating the HAuCl4 and hydroxyl column [5] aromatic hydrocarbons, and then mixed with the microcrystalline cellulose.

Benefits of technology

It realizes the large-scale synthesis of efficient microcrystalline cellulose-supported columnar aromatic/gold nanoparticle catalyst without using solvents and complex purification techniques. It has a simple process, environmentally friendly and excellent catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746928A_ABST
    Figure CN119746928A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a microcrystalline cellulose loaded pillararene / gold nanoparticle catalyst, and relates to the technical field of nanogold catalyst preparation, and the preparation method comprises the following steps: (1) taking 1.5-8 mg of HAuCl4 solid, adding 0.1-0.5 mL of H2O, then adding 16 mg of hydroxyl column [5] arene, and carrying out ultrasonic treatment for 10-15 min; and (2) mixing 200mg of microcrystalline cellulose with the mixture, and grinding for 5-15 minutes to obtain the product. The preparation process is green and environment-friendly, and the prepared product has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-gold catalyst preparation, and in particular to a preparation method and application of a microcrystalline cellulose-loaded pillar aromatics / gold nano-particle catalyst. Background Art

[0002] Gold nanoparticles have high catalytic activity, unique optics, strong affinity, high biocompatibility and excellent structural properties, and are widely used in catalysis and sensors. Pillar aromatics have excellent performance in molecular recognition, self-assembly and other methods. Cellulose is a natural polymer with extremely abundant reserves in nature. It is an important component of plant cell walls and also exists in animal tissues. For example, the tunicate cellulose rich in the dorsal sac of tunicates is the only animal-derived cellulose discovered so far. Cellulose has the advantages of biodegradability, non-toxicity, biocompatibility, low price and wide sources. The polymer nanomaterials prepared with it as raw material can greatly reduce the pressure of subsequent environmental governance and are highly favored in the fields of biomedicine, green catalysis, electronic equipment, environmental governance and so on.

[0003] Therefore, the composite of gold nanoparticles, pillar aromatics and cellulose for the adsorption and treatment of organic pollutants in water bodies can provide a new idea for water pollution control. In the article "Preparation of pillar aromatics / gold nanoparticle-cellulose composite materials and their catalytic and sensing applications", a ternary composite material was also developed, but its preparation method is: first, MCC is treated with hydrogen peroxide to prepare CNCs, and then HAuCl4 and 2HP6 are used in a strong alkaline environment to prepare HP6 / AuNPs, and then CNCs and HP6 / AuNPs are stirred at room temperature and centrifuged. This preparation method not only uses hydrogen peroxide, but also requires a strong alkaline environment, and the preparation process is cumbersome. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for large-scale synthesis of solid microcrystalline cellulose-supported pillararomatic hydrocarbon / gold nanoparticle (AuNP) catalysts without using solvents and complex purification technology to address the deficiencies of the prior art. The preparation process is green and environmentally friendly, and the prepared product has excellent catalytic performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a microcrystalline cellulose-supported pillararomatic hydrocarbon / gold nanoparticle catalyst comprises the following steps: (1) Take 1.5-8 mg of HAuCl4 solid, add 0.1-0.5 mL of H2O, then add 16 mg of hydroxy column [5] aromatic hydrocarbon, and sonicate for 10-15 min; (2) Mix 200 mg of microcrystalline cellulose with the above mixture and grind for 5-15 min to obtain the product.

[0006] Furthermore, the hydroxyl column [5] aromatic hydrocarbon is prepared by the following steps: (1) Add paraformaldehyde and 1,1-dibromophenylene ether to 1,2-dichloroethane respectively, then slowly add boron trifluoride etherate, and stir at room temperature for 1.5-2.5 h. The reaction solution gradually turns dark green. The reaction solution is extracted with dichloromethane, the organic solvent is evaporated under reduced pressure, and column chromatography is performed to obtain an intermediate. (2) Then add the intermediate and cesium carbonate to an appropriate amount of acetonitrile solution, heat and reflux for 20 min, then slowly add N-methyldiethanolamine, and continue to reflux for 36 h; (3) After the reaction is completed, the mixture is cooled to room temperature, the reaction solvent is evaporated, and the crude product is separated and purified by column chromatography using dichloromethane / ethanol / ammonia water as eluent to obtain a light yellow solid to obtain the target product.

[0007] Furthermore, the molar ratio of boron trifluoride ether, paraformaldehyde, and 1,1-dibromophenylene diethyl ether is 25.0:25.0-30.0:13.0; The molar ratio of the intermediate, cesium carbonate and N-methyldiethanolamine is 0.5:4-6:5.0-12.0.

[0008] Application of microcrystalline cellulose-supported pillararene / gold nanoparticle catalyst in the catalytic reduction of p-nitrophenol.

[0009] Furthermore, the product prepared after grinding is used for catalytic reduction of p-nitrophenol within 2 hours.

[0010] The beneficial effects of the present invention are: 1. The present invention discloses a method for preparing a microcrystalline cellulose-loaded pillar aromatics / gold nanoparticle catalyst, which is prepared by mechanical grinding alone, does not require a reducing agent, high temperature, strong acid or strong base conditions, has a simple process, and is in line with the concept of green environmental protection.

[0011] 2. During the grinding process of hydroxyl column [5] aromatic hydrocarbons, microcrystalline cellulose and HAuCl4, the hydroxyl group at the end of hydroxyl column [5] aromatic hydrocarbons acts as a reducing agent to convert HAuCl4 into Au 3+While being reduced to AuNPs, the hydroxyl group may be oxidized to an aldehyde group. Under grinding conditions, the aldehyde group is connected to O-Au, which can also prevent the infinite aggregation of AuNPs. The reduced gold nanoparticles self-assemble under grinding, with an average particle size of 66.78±1.98 nm. They are loaded on microcrystalline cellulose to obtain a microcrystalline cellulose-loaded pillar aromatic hydrocarbon / gold nanoparticle catalyst (Au-P5-MCC), in which the self-assembled AuNPs are evenly distributed on the microcrystalline cellulose. The loading of microcrystalline cellulose can not only improve the solubility of AuNPs in water, facilitate recycling after the reaction, and increase energy-saving and environmental protection effects, but also the microcrystalline cellulose has excellent adsorption properties and can adsorb organic matter to increase the catalytic performance.

[0012] 3. The present application adjusts the preparation process of hydroxyl column [5] aromatics, and the yield and purity of hydroxyl column [5] aromatics are high. Only a small amount of water is added for grinding. The high-purity hydroxyl column [5] aromatics can reduce HAuCl4 without interference from impurities, and can reduce the agglomeration of AuNPs, so that it can have excellent catalytic performance under the simplest preparation conditions. The prepared Au-P5-MCC catalyst has excellent catalytic performance in the process of catalytic reduction of p-nitrophenol, and its rate constant k value is 0.021min −1 .

[0013] 4. The catalytic performance of the products after waiting for 2 h, waiting for 48 h, and heating at 60 °C for 30 min after grinding was studied. The results showed that the catalytic performance was best 2 h after grinding. The possible reason is that the waiting time is too long or heating is performed, and the self-assembly of AuNPs causes the particle size to become larger and aggregate, affecting the catalytic effect. Therefore, when using the catalyst prepared by the preparation process of this application, try to grind it and use it immediately or within 2 h.

[0014] 5. The catalyst prepared in this application can be reused 10 times with almost no change in catalytic performance and high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a flow chart of the preparation process of the present invention; Figure 2 TEM image of the product prepared by the present invention; Figure 3 The size distribution diagram of the gold nanoparticles prepared by the present invention; Figure 4 The color change of p-nitrophenol under the action of Au-P5-MCC; Figure 5 4 (a) is a UV-Vis graph of the catalytic reduction of p-nitrophenol by Au-P5-MCC, 4 (b) is a graph of ln[Ct / C0] as a function of the reaction time for the reduction of p-nitrophenol; Figure 6 The UV-Vis images of the catalytic reduction of p-nitrophenol after the product was ground and then waited for 2 hours, 24 hours, and heated. Figure 7 For hydroxyl-column[5]arene 1 HNMR spectra; Figure 8 For hydroxyl-column[5]arene 13 CNMR image. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with the accompanying drawings and embodiments. Example 1

[0017] A method for preparing a microcrystalline cellulose-supported pillararomatic hydrocarbon / gold nanoparticle catalyst comprises the following steps: (1) Take 7.8 mg of HAuCl4 solid and put it in a 2 mL reagent bottle, add 0.2 mL of H2O, then add 16 mg of hydroxy column [5] aromatic hydrocarbon into the reagent bottle, and sonicate for 15 min; (2) Then, add 200 mg of microcrystalline cellulose to the agate mortar, add the mixture in the reagent bottle to the microcrystalline cellulose, and grind for 10 min to obtain the product, such as Figure 1 As shown, the product is purple-red powder (Au-P5-MCC).

[0018] Hydroxyl column [5] aromatics are prepared by the following steps: (1) Add paraformaldehyde (25.0 mmol) and 1,1-dibromophenylene diethyl ether (13.0 mmol) to 1,2-dichloroethane (200 mL), then slowly add boron trifluoride ether (25.0 mmol) and stir at room temperature for 1.5 h. The reaction solution gradually turns dark green. The reaction solution is extracted with dichloromethane, the organic solvent is evaporated under reduced pressure, and column chromatography is performed to obtain the intermediate. (2) Then, the intermediate (0.5 mmol) and 4 mmol of cesium carbonate were added to an appropriate amount of acetonitrile solution, heated under reflux for 20 min, and then N-methyldiethanolamine (12 mmol) was slowly added and refluxed for 36 h; (3) After the reaction was completed, the mixture was cooled to room temperature, the reaction solvent was evaporated, and the crude product was separated and purified by column chromatography using dichloromethane / ethanol / ammonia water as eluent (the corresponding volume ratio was 30:2:1) to obtain a light yellow solid, which was the target product, with a yield of 98%; The molar ratio of boron trifluoride etherate, paraformaldehyde and 1,1-dibromophenylene diethyl ether is 25.0:25.0:13.0; the molar ratio of the intermediate, cesium carbonate and N-methyldiethanolamine is 0.5:4:12.

[0019] The target product prepared, NMR detection data such as Figure 7 and 8 As shown, 1 H NMR (500 MHz, CDCl3, 25 o C)δ (ppm): 6.82 (s, 10H), 4.01-3.99 (m, 20H), 3.74 (s, 10H), 3.50-3.48 (t,20H), 2.86-2.84 (d, 30H), 2.54-2.51 (t, 20H), 2.33 (s, 30H); 13 C NMR (125 MHz, CDCl3, rt) δ (ppm): 149.92, 128.52, 115.61, 66.84,59.80, 58.79, 57.10, 42.78, 29.53. It was verified that the prepared compound is: Example 2

[0020] A method for preparing a microcrystalline cellulose-supported pillararomatic hydrocarbon / gold nanoparticle catalyst comprises the following steps: (1) Take 1.7 mg of HAuCl4 solid and put it in a 2 mL reagent bottle, add 0.5 mL of H2O, then add 16 mg of hydroxy column [5] aromatic hydrocarbon into the reagent bottle, and sonicate for 15 min; (2) Then, add 200 mg of microcrystalline cellulose to the agate mortar, add the mixture in the reagent bottle to the microcrystalline cellulose, and grind for 15 min to obtain the product (Au-P5-MCC).

[0021] The hydroxyl column [5] aromatic hydrocarbon is prepared by the following steps: (1) Add paraformaldehyde (30.0 mmol) and 1,1-dibromophenylene diethyl ether (13.0 mmol) to 1,2-dichloroethane (200 mL), then slowly add boron trifluoride ether (25.0 mmol) and stir at room temperature for 2.5 h. The reaction solution gradually turns dark green. The reaction solution is extracted with dichloromethane, the organic solvent is evaporated under reduced pressure, and column chromatography is performed to obtain the intermediate. (2) Then, the intermediate (0.5 mmol) and 6 mmol of cesium carbonate were added to an appropriate amount of acetonitrile solution, heated under reflux for 20 min, and then N-methyldiethanolamine (5.0 mmol) was slowly added and refluxed for 36 h; (3) After the reaction was completed, the mixture was cooled to room temperature, the reaction solvent was evaporated, and the crude product was separated and purified by column chromatography using dichloromethane / ethanol / ammonia water as eluent (the corresponding volume ratio was 30:2:1) to obtain a light yellow solid to obtain the target product with a yield of 98.1%; The molar ratio of boron trifluoride etherate, paraformaldehyde and 1,1-dibromophenylene diethyl ether is 25.0:30.0:13.0; the molar ratio of the intermediate, cesium carbonate and N-methyldiethanolamine is 0.5:6:5.0. Example 3

[0022] A method for preparing a microcrystalline cellulose-supported pillararomatic hydrocarbon / gold nanoparticle catalyst comprises the following steps: (1) Take 2.72 mg of HAuCl4 solid and put it in a 2 mL reagent bottle, add 0.1 mL of H2O, then add 16 mg of hydroxy column [5] aromatic hydrocarbon into the reagent bottle, and sonicate for 10 min; (2) Then, add 200 mg of microcrystalline cellulose to the agate mortar, add the mixture in the reagent bottle to the microcrystalline cellulose, and grind for 5 min to obtain the product (Au-P5-MCC).

[0023] The hydroxyl column [5] aromatic hydrocarbon is prepared by the following steps: (1) Add paraformaldehyde (28.0 mmol) and 1,1-dibromophenylene diethyl ether (13.0 mmol) to 1, 2-dichloroethane (200 mL), then slowly add boron trifluoride ether (25.0 mmol) and stir at room temperature for 2.5 h. The reaction solution gradually turns dark green. The reaction solution is extracted with dichloromethane, the organic solvent is evaporated under reduced pressure, and column chromatography is performed to obtain the intermediate. (2) Then, the intermediate (0.5 mmol) and 5 mmol of cesium carbonate were added to an appropriate amount of acetonitrile solution, heated under reflux for 20 min, and then N-methyldiethanolamine (5.0 mmol) was slowly added and refluxed for 36 h; (3) After the reaction is completed, the mixture is cooled to room temperature, the reaction solvent is evaporated, and the crude product is separated and purified by column chromatography using dichloromethane / ethanol / ammonia water as eluent (the corresponding volume ratio is 30:2:1) to obtain a light yellow solid to obtain the target product.

[0024] Performance testing: 1. The product prepared in Example 1 was subjected to TEM testing, see Figure 2 and Figure 3 The average particle size of the gold nanoparticles loaded on microcrystalline cellulose is 66.78±1.98 nm. They are dispersed spherical particles with good morphology, and the loaded product is easy to recycle.

[0025] 2. Au-P5-MCC catalytic reduction of p-nitrophenol Take 69.5 mg of p-nitrophenol and dilute it to 50 mL in a 50 mL volumetric flask; take 189.2 mg of sodium borohydride and dilute it to 50 mL in a 50 mL volumetric flask; take 4 mg of Au-P5-MCC prepared in Example 1 (wait for about 2 h after grinding) and dissolve it in 0.5 mL of H2O; take 0.03 mL of the above p-nitrophenol solution in a quartz cuvette, add 0.2 mL of the above sodium borohydride solution, and then add 2.5 mL of H2O; add 0.5 mL of Au-P5-MCC solution to the cuvette and measure its catalytic performance.

[0026] See also Figure 4 As shown, the color of p-nitrophenol changed from yellow to colorless after adding Au-P5-MCC, and it can be clearly seen that the loaded product sank to the bottom, which is convenient for recycling and reuse.

[0027] Figure 5 This is the UV-Vis graph of the catalytic reduction of p-nitrophenol by Au-P5-MCC. At 13.5 min, Au-P5-MCC almost completely catalyzed the reduction of p-nitrophenol, and the rate constant k The value is 0.021 min −1 .

[0028] Under the same conditions, the products of waiting for 2 h and 24 h after grinding and heating at 60 °C for 30 min after grinding were used for catalytic reduction of p-nitrophenol, and the UV-Vis images after 10 min were shown in Table 1. Figure 6 The catalytic performance is best 2 h after grinding. The possible reason is that the waiting time is too long or heating is performed, and the self-assembly of AuNPs causes the particle size to become larger and aggregate, affecting the catalytic effect. Therefore, in catalytic applications, it is recommended to grind and use it immediately, or use it up within 2 h after grinding, at this time, the catalytic performance is the best.

[0029] In addition, the catalyst of the present application has high stability. After one catalytic reaction, it is recovered and filtered by a centrifuge; after repeating 10 times, its catalytic performance has no obvious change, and it has strong stability and can be repeatedly used for a long time.

[0030] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a microcrystalline cellulose-supported pillararene / gold nanoparticle catalyst, characterized in that: The following steps are involved: (1) Take 1.5-8 mg of HAuCl4 solid, add 0.1-0.5 mL of H2O, then add 16 mg of hydroxy column [5] aromatic hydrocarbon, and sonicate for 10-15 min; (2) Mix 200 mg of microcrystalline cellulose with the above mixture and grind for 5-15 min to obtain the product.

2. The method for preparing a microcrystalline cellulose-supported pillararene / gold nanoparticle catalyst according to claim 1, characterized in that: The hydroxyl column [5] aromatic hydrocarbon is prepared by the following steps: (1) Add paraformaldehyde and 1,1-dibromophenylene ether to 1,2-dichloroethane respectively, then slowly add boron trifluoride etherate, and stir at room temperature for 1.5-2.5 h. The reaction solution gradually turns dark green. The reaction solution is extracted with dichloromethane, the organic solvent is evaporated under reduced pressure, and column chromatography is performed to obtain an intermediate. (2) Then add the intermediate and cesium carbonate to an appropriate amount of acetonitrile solution, heat and reflux for 20 min, then slowly add N-methyldiethanolamine, and continue to reflux for 36 h; (3) After the reaction is completed, the mixture is cooled to room temperature, the reaction solvent is evaporated, and the crude product is separated and purified by column chromatography using dichloromethane / ethanol / ammonia water as eluent to obtain a light yellow solid to obtain the target product.

3. The method for preparing a microcrystalline cellulose-supported pillararene / gold nanoparticle catalyst according to claim 2, characterized in that: The molar ratio of boron trifluoride ether, paraformaldehyde and 1,1-dibromophenylene diethyl ether is 25.0:25.0-30.0:13.0; The molar ratio of the intermediate, cesium carbonate and N-methyldiethanolamine is 0.5:4-6:5.0-12.

0.

4. Use of the microcrystalline cellulose-supported pillararene / gold nanoparticle catalyst prepared according to claim 1 in catalytic reduction of p-nitrophenol.

5. The use according to claim 4, wherein the product prepared after grinding is used for catalytic reduction of p-nitrophenol within 2 hours.

Citation Information

Patent Citations

  • Cellulose-based catalyst with efficient formaldehyde removal effect and preparation method of cellulose-based catalyst

    CN107252703A

  • Gold nanoparticle preparation method

    CN107755710A

  • Method for synthesizing gold nanoparticles by using water-soluble alkaline column [5] arene

    CN116851770A